2018
DOI: 10.1186/s40497-018-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital and entrepreneurial outcomes: the moderating role of social competences of owners of micro-enterprises in East Africa

Abstract: Business success arises out of the total investments in the venture. This is not limited to tangible inputs such as financial capital, but on intangible resources as well. Entrepreneurship is a highly stressing occupation involving undertaking risks and often demanding workloads; hence requiring mental inputs (psychological capital). Moreover, the entrepreneurial job also involves doing business with other people of different statuses including investors, partners, customers, and employees; hence requiring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 101 publications
(154 reference statements)
4
43
0
1
Order By: Relevance
“…In the group of solo self-employed of the BIBB/BAuA employment survey, the lowest value was given for agriculture workers in men (30.10) and cleaners in women (32.20) and the highest for doctors or pharmacists (191.30). Finally, there might be important differences regarding voluntariness of, and hence commitment to, the self-employed role ( Baluku et al, 2018a , b ). As there were no data available concerning the willingness to stay in solo self-employment, we used the unemployment quote by gender as a proxy to have an indicator of a range of difficult economic situations and thus higher or lower employment stability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group of solo self-employed of the BIBB/BAuA employment survey, the lowest value was given for agriculture workers in men (30.10) and cleaners in women (32.20) and the highest for doctors or pharmacists (191.30). Finally, there might be important differences regarding voluntariness of, and hence commitment to, the self-employed role ( Baluku et al, 2018a , b ). As there were no data available concerning the willingness to stay in solo self-employment, we used the unemployment quote by gender as a proxy to have an indicator of a range of difficult economic situations and thus higher or lower employment stability.…”
Section: Methodsmentioning
confidence: 99%
“…Work is essential for gratification of the basic psychological needs of autonomy, competence, and relatedness ( Van den Broeck et al, 2016 ) which in turn foster psychological growth and well-being ( Ryan and Deci, 2001 ; Deci and Ryan, 2008 ; Van den Broeck et al, 2016 ). In terms of self-employment, existing research indicates that entrepreneurs tend to be happier and report high levels of psychological well-being ( Binder and Coad, 2013 ; Baluku et al, 2018a ; Shir et al, 2018 ; Nikolaev et al, 2019 ). In contrast, individuals tend to experience serious mental health challenges such as low self-esteem, substance abuse, and severe mental health concerns when they are out of work ( Blustein, 2008 ; Otto and Dalbert, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cultural orientations are particularly relevant to entrepreneurship because of their relationship to social skills and behavior. Previous research has already demonstrated that social competencies such as the ability to have quality interactions are essential for entrepreneurial success (Baluku, Kikooma, Bantu, & Otto, 2018;Baron & Markman, 2000. In this direction, the present study examines whether cultural intelligence (a socio-cultural competence) mediates the relationship between personal cultural orientations and success in self-employment in a multiethnic context.…”
Section: Introductionmentioning
confidence: 92%
“…According to some studies, itl has a direct positive relationship with business performance (Peterson et al, 2011;Sweetman et al, 2011), success (Culbertson et al, 2010;Baluku et al, 2018) as well as desired psychological outcomes (Avey et al, 2010). Therefore, it is appropriate to assume that a direct relationship exist between psychological capital and business performance, the hypothesis is stated as follows: H1 Positive Psychology Capital has a direct effect on business performance.…”
Section: Positive Psychology Capital and Business Performancementioning
confidence: 99%
“…It is usually valued when challenges such as an increase in financial capital are substantially dependent on endurance capital (that is, a collection of personal resources used for family businesses). It is also a strategic resource that affects both economic and non-economic performances (Baluku et al, 2018).…”
Section: Introductionmentioning
confidence: 99%